‘A festival of the Canadian Writer’ or on the Lesser Known Polish Translations of Anne of Green Gables by Lucy Maud Montgomery - Pielorz, Dorota (Porównania, 2020)
The article deals with Polish translations of Lucy Maud Montgomery’s book Anne of Green Gables. The author focuses especially on the renderings published at the turn of the 21st century, when the so called “festival of the Canadian writer” began. This phrase is used in reference to the renascence of the popularity of Montgomery’s work in Poland. This cultural and marketing phenomenon not only affected readers, but also influenced the publishers’ and translators’ choices. In the article, some dimensions of this casus are discussed. Then some excerpts of translations are compared in order to show the features of the image of Canada inscribed in them by translators. What is more, the author points out that the Polish renderings can provide interesting information about the different aspects of Polish reality at the turn of the 21st century, in particular about the publishing policies and the Polish culture, aesthetic norms and trends or stereotypes.